2016
DOI: 10.3389/fpls.2016.00312
|View full text |Cite
|
Sign up to set email alerts
|

Floral Volatiles in Parasitic Plants of the Orobanchaceae. Ecological and Taxonomic Implications

Abstract: The holoparasitic broomrapes, Orobanche spp. and Phelipanche spp. (Orobanchaceae), are root parasites that completely depend on a host plant for survival and reproduction. There is considerable controversy on the taxonomy of this biologically and agronomically important family. Flowers of over 25 parasitic Orobanchaceae and a number of close, parasitic and non-parasitic, relatives emitted a complex blend of volatile organic compounds (VOCs), consisting of over 130 VOCs per species. Floral VOC blend-based phylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…In accordance with agrobiological classification [7], annual and perennial nonparasitic weeds were found around utility poles [8]. Annual weeds are characterized by seed reproduction, life cycle of no more than 2 years, and die right after seeds develop.…”
Section: Methodsmentioning
confidence: 71%
“…In accordance with agrobiological classification [7], annual and perennial nonparasitic weeds were found around utility poles [8]. Annual weeds are characterized by seed reproduction, life cycle of no more than 2 years, and die right after seeds develop.…”
Section: Methodsmentioning
confidence: 71%
“…HCA based on volatile content has been used to explore taxonomic relatedness in other plant systems, including citrus [Citrus sp. (Jing et al, 2015;Zhang et al, 2017)], parasitic plants [Orobanchaceae (Toth et al, 2016)], blueberries [Vaccinium sp. (Gilbert et al, 2015)], and Cymbopogon grasses (Khanuja et al, 2005); however, the results of clustering based solely on volatile profiles do not always coincide with established taxonomy.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers agree that Orobanche spp. differ in the presence of metabolites in trichome cells: El-Akkad et al (2002) and Hassan and El-Awadi (2009) detected the presence of lipid, lignin, phenolic, and suberin materials, Sacchetti et al (2003) described the content of terpenes and flavonoids, Hegnauer (1990) identified iridoid glycosides and sesquiterpenes, Serafini et al (1995) demonstrated the presence of phenylpropanoid glycosides, and Tóth et al (2016) detected floral volatile organic compounds. The authors of the present study believe that the presence of alkaloids as well as tannins and flavonoids in the O. picridis trichomes provides protection to these plants against herbivore foraging and fungal or bacterial diseases.…”
Section: Trichome Microstructure and Histochemistrymentioning
confidence: 99%
“…Bumblebees, Colletid and Halictid bees, wasps, and stiletto flies visit Orobanche flowers from early morning to late afternoon (Jones 1991;Toth et al 2013). The flowers attract insects with their fragrance (Hegnauer 1990;Piwowarczyk et al 2015;Tóth et al 2016) and offer pollen and nectar reward (Saghir and Dastgheib 1978;Ollerton et al 2007). Annular nectaries in Orobanche flowers are located at the base of the ovary (Kreutz 1995;Bekker and Kwak 2005;Fahmy 2013).…”
Section: Introductionmentioning
confidence: 99%